2021
DOI: 10.1093/ve/veab087
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological dynamics of SARS-CoV-2 VOC Gamma in Rio de Janeiro, Brazil

Abstract: The emergence and widespread circulation of SARS-CoV-2 variants of concern (VOC) or interest (VOI) imposes an enhanced threat to global public health. In Brazil, one of the countries most severely impacted throughout the pandemic, a complex dynamics involving variants co-circulation and turnover events has been recorded with the emergence and spread of VOC Gamma in Manaus in late 2020. In this context, we present a genomic epidemiology investigation based on samples collected between December 2020 and May 2021… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…The pipeline for sequencing data processing was performed as previously described [ 17 ], which includes: (i) Filtering and trimming reads and adapters using fastp v.0.20.1 [ 20 ]; (ii) mapping the sequences with the reference genome (NCBI RefSeq SARS-CoV-2; accession number: NC_045512) with Bowtie2 v2.4.2 [ 21 ]; (iii) sorting and indexing the mapped files with SAMtools v1.12 [ 22 ]; (iv) variant calling and consensus genome inference using the BCFtools v1.12; and (v) mask sites with depth less than 10× with BEDtools v2.30.0. Sequences with less than 70% coverage were removed from the analysis [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pipeline for sequencing data processing was performed as previously described [ 17 ], which includes: (i) Filtering and trimming reads and adapters using fastp v.0.20.1 [ 20 ]; (ii) mapping the sequences with the reference genome (NCBI RefSeq SARS-CoV-2; accession number: NC_045512) with Bowtie2 v2.4.2 [ 21 ]; (iii) sorting and indexing the mapped files with SAMtools v1.12 [ 22 ]; (iv) variant calling and consensus genome inference using the BCFtools v1.12; and (v) mask sites with depth less than 10× with BEDtools v2.30.0. Sequences with less than 70% coverage were removed from the analysis [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…These initiatives allowed the establishment of specific SARS-CoV-2 databases [ 13 ] that accelerated vaccine development [ 14 ]. Several regional initiatives have also emerged in Brazil to collect information associated with the COVID-19 pandemic [ 10 , 15 , 16 , 17 ]. However, due to its enormous territorial extension, a national unified genomic surveillance system is urgent to expand and connect the regional data in real-time.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the Zeta lineage was identified for the first time in July 2020 in RJ 23 , and it became predominant in this State from December 2020 until January 2021. This pattern changed after the emergence of the P.1 lineage, after its first detection 19 . As in RJ, in ES there was cocirculation of important lineages together with the Zeta lineage, such as B.1.1.33, B.1.1.28, Alpha and Gamma .…”
Section: Discussionmentioning
confidence: 96%
“…Lineages B.1.1.28 and B.1.1.33 had the highest percentages in the country (n=156, 31.01%, and 26.04%, respectively). In Rio de Janeiro, a study conducted with samples collected on December 1, 2020 and May 12, 2021 19 identified lineages P.2 (43.44%), P.1 (36.47), B.1.1 (5.73%), B .1 (3.69%), B.1.1.28 (3.28%), P.1.2 (3.28%), B.1.1.33 (1.23%), B.1.1.7 (1.23%), P.4 (0.82%, B.1,407 (0.41%) and N.9 (0.41%). The predominant lineage in Rio de Janeiro was Zeta , which occurred between December 2020 and January 2021, followed by P. 1, which was detected in the sixth week of 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Illumina sequencing proceeded using two distinct protocols for library construction, as described in Orf et al (2021) and Moreira et al (2021). Briefly, viral RNA was converted to cDNA with SuperScript IV (ThermoFisher, USA) and whole genome amplification was performed with the ARTIC SARS-CoV-2 V3 primer panel and the Q5 hotstart polymerase (NewEnglandBiolabs, USA).…”
Section: Sequencing and Phylogenetic Analysismentioning
confidence: 99%